Fish Assemblages of a Sub-Arctic Fjord Show Early Signals of Climate Change Response Contrary to the Benthic Assemblages - Mérillet, Laurène; Skogen, Morten D.; Vikebø, Frode; Jørgensen, Lis Lindal (Frontiers in Marine Science, 2022)
Arctic benthic ecosystems are facing high-speed environmental changes, such as decreased sea ice coverage, increased temperature and precipitations, as well as the invasion by non-indigenous species. Few sub-arctic fjords have the particularity to have an inner-most part forming a basin in which water remains very cold. Those fjords may offer a refugee for cold-water arctic species as well as a small-scale “laboratory” of the changes that arctic assemblages located at higher latitudes might face soon. The Porsangerfjord in Northern Norway is a sub-arctic fjord with an inner arctic part and face red king crabs Paralithodes camtchasticus invasion since the end of the 1990s. It offers a case study of the dynamics of arctic ecosystems facing multiple stressors, i.e., climate change and invasive species. Based on a time series of megabenthic invertebrates and bentho-demersal fishes over 2007–2019, a complex multivariate analysis (STATICO) was used to identify the trends in the relationship between taxa and the environment. We showed the main environmental changes in the fjord were the freshening of the water, the increase of the seabed current, and the decrease of the maximum sea ice extent. A strong along-fjord gradient was visible for both benthic and fish assemblages. Species richness and Shannon diversity of fishes significantly increased into the fjord, due to the arrival of warm-water species over time that overlapped with cold-water species that have seen their biomass significantly reduced. No significant decrease in the biomass of the cold-water benthic species was visible, which could indicate an efficient refugee effect of the inner fjord. Yet, this refugee effect could be unbalanced by the red king crab invasion as it is a predator of several arctic species. In the Porsangerfjord, fish species thus respond to climate change while megabenthic assemblages are more threatened by invasive species.